Biofilm-associated proteins: from the gut biofilms to neurodegeneration - Jaione Valle (Gut Microbes)
Human microbiota form a biofilm with substantial consequences for health and disease. Numerous studies have indicated that microbial communities produce functional amyloids as part of their biofilm extracellular scaffolds. The overlooked interplay between bacterial amyloids and the host may have detrimental consequences for the host, including neurodegeneration. This work gives an overview of the biofilm-associated amyloids expressed by the gut microbiota and their potential role in neurodegeneration. It discusses the biofilm-associated proteins (BAPs) of the gut microbiota, maps the amyloidogenic domains of these proteins, and analyzes the presence of bap genes within accessory genomes linked with transposable elements. Furthermore, the evidence supporting the existence of amyloids in the gut are presented. Finally, it explores the potential interactions between BAPs and α-synuclein, extending the literature on amyloid cross-kingdom interactions. Based on these findings, this study propose that BAP amyloids act as transmissible catalysts, facilitating the misfolding, accumulation, and spread of α-synuclein aggregates. This review contributes to the understanding of complex interactions among the microbiota, transmissible elements, and host, which is crucial for developing novel therapeutic approaches to combat microbiota-related diseases and improve overall health outcomes.